Pemphigus - A clinical study with clinico-immuno-histopathologic correlation - P N Mini; M S Sadeep (Wolters Kluwer Medknow Publications, 2019)
Background: Pemphigus is a group of autoimmune blistering disease of the skin and mucous membranes with an incidence of <2 cases per 100,000 population. The aim is to evaluate the clinical pattern and to study the correlation between clinical, histopathological, and immunofluorescence findings in pemphigus. Materials and Methods: All newly registered patients with flaccid blisters and erosions on the skin with/without oral erosions during 2 years from May 2009 to April 2011 were evaluated by detailed history, clinical examination, cytological, pathological, and direct immunofluorescence studies, and results correlated. Results: Of the 43 patients studied, 36 (83.72%) had pemphigus vulgaris and 7 (16.28%) had pemphigus foliaceus with maximum patients in the age group of 40-59 years and M:F ratio of 1:1.3. Cytologically, acantholytic cells were demonstrated in 88.37%, histopathological correlation was seen in 100% cases, and direct immunofluorescence was positive in 97.37% of the 38 cases in which it was performed. Conclusion: Clinico-immuno-histopathologic correlation is seen in most cases of pemphigus, and although a combination of clinical, cytological, histopathological, and immunofluorescence findings virtually eliminates the chances of error in the diagnosis of pemphigus, histopathology may suffice in most cases.